USING BRAND IMAGE AS A MEDIATOR, THE INFLUENCE OF SOCIAL MEDIA MARKETING AND BRAND AMBASSADORS ON FLIMY'S INTENTION TO BUY - Lee, Patricia Claresta; Saktiana, Galuh Mira (International Journal of Application on Economics and Business, 2025)
In the era of globalization, it has had many impacts on human life and the world. For that, it is not only technology that brings changes to people today, but there are still many other things that are considered, such as one of them is appearance. An ideal body is everyone's dream, not only women who crave an ideal shape and weight, men certainly want to have an ideal shape and weight by consuming fiber drink products. From this research, there is a research objective, namely to test the influence of brand ambassador variables, social media marketing variables on the variable of interest in purchasing Flimty Fiber beverage products in DKI Jakarta which is mediated by brand image. The sample consisted of 200 respondents. The research data was processed using SmartPLS version 4.0.9.9. Brand ambassadors, social media marketing, and brand image certainly have a positive and significant effect on purchasing interest in flimty fiber beverage products in DKI Jakarta. The research written here is expected to help fiber beverage companies in increasing purchasing interest even more.